2022
DOI: 10.3389/fphar.2021.753803
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Serum Alkaline Phosphatase and Folic Acid Treatment on Chronic Kidney Disease Progression in Treated Hypertensive Adults

Abstract: The relation of alkaline phosphatase (ALP) with chronic kidney disease (CKD) is still uncertain. We aimed to examine the prospective association between serum ALP and CKD progression, and the modifying effect of serum ALP on folic acid in preventing CKD progression in treated hypertensive patients. This is a post-hoc analysis of 12,734 hypertensive adults with relevant measurements and without liver disease at baseline from the renal sub-study of the China Stroke Primary Prevention Trial, where participants we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
1
0
0
Order By: Relevance
“…The relationship between enalapril maleate and hypertension has become the focus of attention by medical scholars all over the world. Recent studies have found that enalapril maleate folic acid tablets also reduced arterial sclerosis in patients with hypertension [11]. In the present study, MAP, aortic middle thickness, LVWI and HWI of rats were markedly decreased by enalapril maleate folic acid.…”
Section: Discussionsupporting
confidence: 61%
“…The relationship between enalapril maleate and hypertension has become the focus of attention by medical scholars all over the world. Recent studies have found that enalapril maleate folic acid tablets also reduced arterial sclerosis in patients with hypertension [11]. In the present study, MAP, aortic middle thickness, LVWI and HWI of rats were markedly decreased by enalapril maleate folic acid.…”
Section: Discussionsupporting
confidence: 61%